US Tight Oils – prospects and implications - Sen, A (Oxford Institute for Energy Studies, 2013)
This paper examines the implications of the rapid growth in US tight oil production for US and global energy markets. The behaviour of US crude markets is analysed, with a particular focus on changing arbitrage dynamics. The rapid growth in US tight oils production was not met with an equally fast response by the US midstream companies, resulting in severe regional crude price dislocations. These lower regional prices impacted on producer profits and, more significantly, benefitted refineries that secured cheap feedstock and sold end products at levels linked to global product markets. However, we argue that globally, US tight oil production has primarily impacted price spreads though changes in trade flows, rather than absolute oil price levels, given various offsetting factors such as extremely weak supplies from outside the US.‎ Put another way, we argue that perhaps the correct way of seeing the US supply shock is not as something that should result in the collapse of prices, but instead as a factor that has prevented prices from being significantly higher.